"In situ" XPS studies of laser-induced surface nitridation and oxidation of tantalum. Issue 19 (14th July 2015) - Lahoz, Ruth; Espinós, Juan Pedro; Yubero, Francisco; González-Elipe, Agustín Rodríguez; de la Fuente, Germán Francisco
Abstract: Abstract : This work studies the nitridation of Ta by laser irradiation by means of x-ray photoelectron spectroscopy. The study has been carried out under "in situ" conditions by controlling the nitrogen partial pressure, the presence of traces of oxygen, and the irradiance of the laser. It is found that a thin layer of Ta2 O5 is directly obtained when irradiating in the presence of oxygen, while a Ta3 N5 surface compound and some minor contributions of nonstoichiometric phases are formed in the presence of nitrogen. For O2 :N2 mixtures at 0.1 Pa, preferential nitride formation occurs up to a ratio of 1:4, while Ta2 O5 starts to be predominant for ratios above this value. The air stability of the tantalum nitride layer formed by laser irradiation and the surface topography of the irradiated metal are also studied. The possible factors determining this behavior are discussed.